2023
DOI: 10.1146/annurev-criminol-030920-120002
|View full text |Cite
|
Sign up to set email alerts
|

LatCrit and Criminology: Toward a Theoretical Understanding of Latino/a/x Crime and Criminal Legal System Involvement

Abstract: An important body of work documents how race matters for the patterning of crime and criminal legal system involvement largely by focusing on comparisons between Blacks and Whites. We build on this vital scholarship by spotlighting Latino/a/xs, a fast-growing group that is the United States’ largest racial minority, to broaden the field's understanding of race and crime. In this review, we follow race scholars who see Latino/a/xs as a racial category because dominant actors racialize them as an innate, distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…Yet, Blalock argued economic competition would drive this reaction, and this does not appear to be the case as White–Hispanic unemployment ratios did not moderate the relationship between IGSAs and Hispanic arrest rates. Using the perspective articulated by Stucky (2012) and Vélez and Peguero (2023), larger Hispanic populations could lead to greater bureaucratic representation and protection of Hispanic interests that limit arrest exposure. Another possibility is that officers in counties with large Hispanic populations may use other differentiating factors, such as skin color, occupation, or language as a proxy for immigrant status (Armenta, 2017; Donato & Rodriguez, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, Blalock argued economic competition would drive this reaction, and this does not appear to be the case as White–Hispanic unemployment ratios did not moderate the relationship between IGSAs and Hispanic arrest rates. Using the perspective articulated by Stucky (2012) and Vélez and Peguero (2023), larger Hispanic populations could lead to greater bureaucratic representation and protection of Hispanic interests that limit arrest exposure. Another possibility is that officers in counties with large Hispanic populations may use other differentiating factors, such as skin color, occupation, or language as a proxy for immigrant status (Armenta, 2017; Donato & Rodriguez, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research, however, has identified curvilinear relationships that accord with Blalock's economic competition scenario for other types of social control, such as police expenditures (Holmes et al, 2008;Jackson, 1986Jackson, , 1989. Rather than reflect dwindling attempts at economic discrimination, however, scholars have argued that these relationships may stem from minority groups forming an empowered voting block with the ability to change the allocation of resources (Stucky, 2012;Vélez & Peguero, 2023). That is, social control efforts may diminish when minority groups, because of their relative size, begin to exert political influence.…”
Section: Minority Threatmentioning
confidence: 99%
“…For example, Latinx populations in particular may be hesitant to bring attention to family or other community members who may not themselves be fully documented. Furthermore, from a Latinx critical criminology perspective, Vélez and Peguero [97] point out there is an overall perception among some that Latinx communities have been criminalized, which discourages trust in formal institutions. In particular, Latinx "enclaves" tend to undergo increased surveillance and experience more frequent ICE raids, despite overall lower crime rates in these communities [98].…”
Section: Discussionmentioning
confidence: 99%
“…Latinx people are the largest ethnic minority group in the U. S. with 62.5 million people or approximately 19% of the population (Moslimani & Noe‐Bustamente, 2023), but there is a lack of focus on Latinxs and criminal justice system (CJS) disparities (Luna, 2002). Such a focus is imperative because Latinx people endure discrimination at all levels within the CJS (Valencia et al., 2004; Velez & Peguero, 2023). One in six Latinx people born in 2001 can expect to go to prison (Rovner, 2016).…”
Section: Introductionmentioning
confidence: 99%